A Simplified Method for Immunological Typing of Trachoma-Inclusion Conjunctivitis-Lymphogranuloma Venereum Organisms - Wang, San-Pin (1973)
Responding to the pressure of large numbers of trachoma-inclusion conjunctivitis (TRIC)-lymphogranuloma venereum (LGV) isolates from field studies requiring serotyping, we have developed a simplified, less-precise method that utilizes cell culture-grown organisms to produce mouse antisera which is tested agaist prototype TRIC-LGV antigens in the micro-immunofluorescence test. Cell cultures with as few as 5 to 15% of cells showing inclusions produced adequate antibody in mice 4 days after single injection. Knowledge of the reaction of prototype antisera with the antigens has allowed typing of most isolates tested from the pattern of cross-reaction of their antiserum.